1994
DOI: 10.1139/g94-092
|View full text |Cite
|
Sign up to set email alerts
|

Genome size variation in Pisum sativum

Abstract: Pisum sativum L. is one of the plant species where infraspecific genome size variation, up to 1.29-fold between cultivars, has been reported. The present investigation deals with a Feulgen cytophotometric analysis of this phenomenon in 25 wild accessions, landraces, and cultivars of widely different geographic origin. Differences between accessions were maximally 1.054-fold in single experiments but proved to be nonreproducible upon repeated measurements. Seedlings of the same accession often differed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
116
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(120 citation statements)
references
References 31 publications
3
116
1
Order By: Relevance
“…(1994). One test was made with formaldehyde as fixative (see Greilhuber, 1986Greilhuber, , 1987and Greilhuber & Ebert, 1994 for the rationale). Again, no difference between the culti- vars was evident ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1994). One test was made with formaldehyde as fixative (see Greilhuber, 1986Greilhuber, , 1987and Greilhuber & Ebert, 1994 for the rationale). Again, no difference between the culti- vars was evident ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Feulgen densitometry followed Greilhuber & Ebert (1994); details are explained in Tables 1 and 2. Because of the low genome size in soybean, metaphases in side view were measured to obtain a reasonable amount of absorbance.…”
mentioning
confidence: 99%
“…sativum is particularly striking given the 10 times larger genome (26) and one less chromosome in Pi. sativum.…”
Section: Discussionmentioning
confidence: 99%
“…The density of stain of each white clover population was determined in 30 early-prophase nuclei (10 on each of three slides) at 560 nm, using a Vickers M85 scanning microdensitometer, with modifications to correct for errors from glare (Goldstein 1981). Determinations were made within 10 days of preparing the slides to prevent effects of ageing on the intensity and regularity of the Feulgen staining (Greilhuber & Ebert 1994). The repeatability of determinations was also checked (as recommended by Bennett & Leitch 1995) by making identical preparations for two of the populations at the University of Sheffield, UK and measuring nuclear DNA amounts there using a Vickers M85A scanning microdensitometer.…”
Section: Determination Of Nuclear Dna Amountmentioning
confidence: 99%
“…It was suggested that individuals of P. annua with larger DNA amounts would be expected to develop more rapidly under winter and early spring conditions, providing a temporary advantage sufficient to evade competition from the potentially faster growing individuals with lower DNA amounts. However, it should be noted that Greilhuber & Ebert (1994) and Bennett & Leitch 16 New Zealand Journal of Agricultural Research, 1999, Vol. 42 (1995 have recently questioned whether reports of such very large differences in genome size within species (of the order of 100% to 288%) may in part reflect inaccuracies in staining methodology.…”
Section: Differences In Nuclear Dna Amountmentioning
confidence: 99%